2021
DOI: 10.1007/s10854-021-06656-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved magnetic properties of iron-based soft magnetic composites with a double phosphate-SiO2 shells structure

Abstract: Herein a double shells structure was proposed to overcome the drawbacks such as poor heat resistance, incomplete insulation and high core loss coating of ironbased soft magnetic composites (SMCs) with single shell structure. The surface of the iron powder was coated with a double shells structure composed of an inner phosphate coating and an outer SiO 2 coating through phosphating and hydrolysis successively. Subsequently, the effects of different SiO 2 addition amount on the microstructure of iron powder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Choi et al [17] prepared Al 2 O 3 insulating layers of varying thicknesses on the surface of Fe-Si-Cr alloy powders using the sol-gel method, thereby fabricating a composite with an effective permeability of 33.9 and a loss of 252 mW/cm 3 at 50 mT and 100 kHz. Although previous studies [18][19][20][21] have demonstrated that metal oxides are promising candidates for use as insulating layers in the production of Fe-based SMCs, recent studies have predominantly focused on developing new metal oxide insulating layers and improving the properties of Fe-based SMCs [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al [17] prepared Al 2 O 3 insulating layers of varying thicknesses on the surface of Fe-Si-Cr alloy powders using the sol-gel method, thereby fabricating a composite with an effective permeability of 33.9 and a loss of 252 mW/cm 3 at 50 mT and 100 kHz. Although previous studies [18][19][20][21] have demonstrated that metal oxides are promising candidates for use as insulating layers in the production of Fe-based SMCs, recent studies have predominantly focused on developing new metal oxide insulating layers and improving the properties of Fe-based SMCs [22,23].…”
Section: Introductionmentioning
confidence: 99%